Optimización del plan de mantenimiento para el sistema de bombas principales en la estación de bombeo Rubiales para la empresa Oleoducto de los Llanos S.A (2021)
The main objective of this document is to prepare an optimization of the maintenance plan for the main pump system located at the Rubiales pumping station of the ODL company. With this, it will be possible to reduce the maintenance expenses developed in the equipment, with this it is also achieved that preventive maintenance activities are carried out in the appropriate times and reduce corrective stops, maintenance management is also developed to identify the causes and effects that represent the failures generated in the equipment.